Weight loss for obese patients as a treatment of hip and knee osteoarthritis: A scoping review - Megan Cull (Journal of Metabolic Health)
Background: The American Academy of Orthopaedic Surgeons (AAOS) has been recommending a weight loss of 5% of body weight or more as a treatment for those who have osteoarthritis (OA). However, the AAOS does not recommend or guide clinicians in the best weight loss strategies, leaving the clinician and the patients on their own to navigate the weight loss process.